Nigella sativa L. as an alternative antibiotic feed supplement and effect on growth performance in weanling pigs. (2nd February 2018) - Petrujkić, Branko T; Beier, Ross C; He, Haiqi; Genovese, Kenneth J; Swaggerty, Christina L; Hume, Michael E; Crippen, Tawni L; Harvey, Roger B; Anderson, Robin C; Nisbet, David J
Abstract: BACKGROUND: Nigella sativa L. ( NS ) is a plant containing bioactive constituents such as thymoquinone. Extracts of NS improve performance and reduce enteropathogen colonization in poultry and small ruminants, but studies with swine are lacking. In two different studies oral administration of NS extracts at doses equivalent to 0, 1.5 and 4.5 g kg −1 diet was assessed on piglet performance and intestinal carriage of wildtype Escherichia coli and Campylobacter, and Salmonella Typhimurium. RESULTS: Wildtype E. coli populations in the jejunal and rectal content collected 9 days after treatment began were decreased ( P ≤ 0.05). Populations recovered from pigs treated with extract at 1.5 and 4.5 g kg −1 diet were 0.72–1.31 log10 units lower than the controls (ranging from 6.05 to 6.61 log10 CFU g −1 ). Wildtype Campylobacter and Salmonella Typhimurium were unaffected by NS treatment. Feed efficiency over the 9 days improved linearly ( P < 0.05) from 3.88 with 0 NS ‐treated pigs to 1.47 and 1.41 with pigs treated with NS at 1.5 and 4.5 g kg –1 diet, respectively, possibly due to high glutamine/glutamic acid content of the NS extract. CONCLUSION: NS supplementation of weanling pigs improved feed efficiency and helped control intestinal E. coli during this vulnerable production phase. © 2017 Society of Chemical Industry